Imobilização de β-Galactosidases em membranas de óxido de grafeno - Luzardo, Jéssica Menezes de Mélo (2019)
The use of enzymes as catalysts requires recovery and reuse to make the process viable. Enzymatic immobilization changes enzyme stability, activity and specificity. There is no single method or support applicable to all enzymes and their various applications. It is very important to explore new substrates for immobilization with appropriate composition and structure in order to improve the efficiency of the immobilized enzymes. In this work, the use of graphene oxide membranes produced by chemical route (GO) and electrochemistry (EG) for immobilization of β-Galactosidases was investigated. For the membrane’s characterization, the techniques of atomic force microscopy, Raman spectroscopy, X-ray excitation and X-ray diffraction spectroscopy were used. The electrochemical technique of cyclic voltammetry was used to monitor the reaction of conversion of lactose to glucose as well as to evaluate the influence of the use of plasma treatment on the membranes. The AFM images showed that the EG membranes had better immobilization of the enzymes on the surface. This membrane was treated with different plasmas to obtain improved substrates, however, the argon plasma was destructive and the plasma jet contributed to the reduction of the defects of the graphene sheets, interfering in the interaction between the same and the active center of the enzymes, making it difficult to evaluate the activity by cyclic voltammetry. Finally, the unmodified EG membrane was the best substrate for immobilization.